2016
DOI: 10.3906/tar-1407-33
|View full text |Cite
|
Sign up to set email alerts
|

Determination of forage quality by near-infrared reflectance spectroscopy in soybean

Abstract: Soybeans have been a favored livestock forage for centuries. However, only a few studies have been conducted to estimate the forage quality of soybean by near-infrared reflectance spectroscopy (NIRS). In this study, 353 forage soybean samples were used to develop near-infrared reflectance (NIR) equations to estimate four forage quality parameters: crude protein (CP), crude fat (CF), neutral detergent fiber (NDF), and acid detergent fiber (ADF). Samples included 181 recombinant inbred lines derived from PI 4834… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 35 publications
4
29
2
3
Order By: Relevance
“…For example, NIRS has been successfully used to predict the nutritive value of forages and hays through direct scanning of the forage samples or the extrusa obtained from esophageally fistulated animals [9]- [17]. Several other reports have also demonstrated successful application of NIRS in the analysis of anti-quality factors in forage [18]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, NIRS has been successfully used to predict the nutritive value of forages and hays through direct scanning of the forage samples or the extrusa obtained from esophageally fistulated animals [9]- [17]. Several other reports have also demonstrated successful application of NIRS in the analysis of anti-quality factors in forage [18]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the RPDc for all the calibrations were > 3.4 supporting the validity of the NIRS calibration models for routine analysis of the forage attributes measured. These RPDc values for the measured attributes were higher than the values reported previously (Alomar et al, 2009;Asekova et al, 2016;Campo et al, 2013;Cozzolino et al, 2006;Norman et al, 2015;Park et al, 1998) but lower than the RPDc for DMD and total N reported by Norman et al (2015) in temperate forages.…”
Section: Reference Values and Equation Developmentcontrasting
confidence: 53%
“…In the present study this criteria was met for all measurements except for the total N concentration prediction in soybean residue. Satisfactory RPDv values have been reported for total N and NDF and ADF prediction in soybean (Asekova et al, 2016). The poor prediction of the total N concentration in soybean in the present study may have been associated with the small population size (n=25) and that this material tends to be spectrally different to the other forages and crop residues.…”
Section: Equation Performancementioning
confidence: 47%
“…The NIRS technique has not been exploited for forage quality predictions in soybean. A single report investigated modified PLS and multiple scatter correction methods for NIR predictions of CP, NDF, and ADF concentrations, using 353 soybean samples collected at one (R6) growth stage [31]. In comparison, calibrations developed in the present study, used data on IVTD and CP with just 70 soybean samples collected across a range of different growth stages.…”
Section: Soybeanmentioning
confidence: 99%